Vantage perspective in analogue trauma memories: an experimental study. Issue 6 (18th August 2019) - Mooren, Nora; Krans, Julie; Näring, Gérard; van Minnen, Agnes
ABSTRACT: Vantage perspective during recall is thought to affect the emotionality and accessibility of distressing memories. This study aimed to test the effects of vantage perspective during recall on memory associated distress and intrusion development. An adapted version of the trauma film paradigm was used in an experimental design with three conditions. Participants were asked to listen to eyewitness reports of car accidents (e.g. Trauma Analogue Induction) and imagine the scenes vividly using mental imagery. Afterwards, they were asked to recall the most distressing scene from field perspective, observer perspective, or to recall a neutral image from observer perspective (control condition) (e.g. Trauma Analogue Recall). Recall from field perspective resulted in higher negative mood, state-anxiety, and a higher number of short-term intrusions compared to the observer perspective condition and control condition. Negative mood and state-anxiety were mediators in the relationship between vantage perspective and intrusions. In comparison to observer perspective, field perspective increased the amount of short-term intrusions as a result of higher levels of negative mood and state-anxiety after memory retrieval. Future research on the interaction between vantage perspective at recall and negative mood and anxiety effects is warranted.